Within versus between-lake variability of sedimentary diatoms: the role of sampling effort in capturing assemblage composition in environmentally heterogeneous shallow lakes - Hassan, Gabriela Susana (2018)
The effect ofwithin-lake diatom assemblages variability on sample representativity and itssubsequent impact on between-lake comparisons were addressed in threeenvironmentally heterogeneous shallow lakes from the Argentinean Pampas.Surface sediment samples were collected from the open waters and the highlyvegetated littoral areas on a seasonal basis and analyzed for diatomassemblages composition. Within-lake variability was assessed by comparing the BrayCurtis distances between original data and the Monte Carlo-simulated averageassemblages composition through non-metric multidimensional scaling (NMDS). Diatomassemblages showed a high variability in composition, evidencing large dispersions of samples around the centroid in NMDS plots. Permutational Multivariate Analysis of Variance(PERMANOVA) tests signaled significant differences in average compositionbetween the three lakes, related mainly to their differences in conductivityand depth.